Democratic Republic of Sao Tome and Principe : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report; and Press Release on the Executive Board Consideration. (IMF Staff Country Reports; Country Report, 2006)
In 2005, the overall macroeconomic performance was broadly satisfactory, notwithstanding an increase in inflation. All performance criteria were met. Structural reforms advanced, and delays in preparing feasibility studies for restructuring the airport and seaport authorities are being addressed. Economic performance in 2005 was broadly satisfactory, although inflation accelerated. The fiscal program is designed to protect pro-poor spending. The program assumes a broadly stable velocity of circulation of money. The macroeconomic outlook and the program are subject to risks.